(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes an operational founded model for portfolio optimization. The procedure used is based on the redacting ofthe asymmetry impact of the variance. This is a new approach that givesassets more accurate risk measures. The risk adjustment is based on the measure of volatility skewness andthe goal here is to eliminate noisy risk.Moreover, we give our risk asymmetrical effect,according to the means of each asset.